Ethnicity recording in primary care computerised medical record systems: an ontological approach. Issue 4 (1st October 2016) - Tippu, Z; Correa, A; Liyanage, H; Van Vlymen, J; Burleigh, D; McGovern, A; Jones, S; de Lusignan, S
Abstract : Background: Ethnicity recording within primary care computerised medical record (CMR) systems is suboptimal, exacerbated by tangled taxonomies within current coding systems. Objective: To develop a method for extending ethnicity identification using routinely collected data. Methods: We used an ontological method to maximise the reliability and prevalence of ethnicity information in the Royal College of General Practitioner's Research and Surveillance database. Clinical codes were either directly mapped to ethnicity group or utilised as proxy markers (such as language spoken) from which ethnicity could be inferred. We compared the performance of our method with the recording rates that would be identified by code lists utilised by the UK pay for the performance system, with the help of the Quality and Outcomes Framework (QOF). Results: Data from 2, 059, 453 patients across 110 practices were included. The overall categorisable ethnicity using QOF codes was 36.26% (95% confidence interval (CI): 36.20%–36.33%). This rose to 48.57% (CI:48.50%–48.64%) using the described ethnicity mapping process. Mapping increased across all ethnic groups. The largest increase was seen in the white ethnicity category (30.61%; CI: 30.55%–30.67% to 40.24%; CI: 40.17%–40.30%). The highest relative increase was in the ethnic group categorised as the other (0.04%; CI: 0.03%–0.04% to 0.92%; CI: 0.91%–0.93%). Conclusions: This mapping method substantially increases the prevalence of known ethnicity in CMR data and may aid future epidemiological research based on routine data.